Multiseptate Gallbladder, a Rare Cause of Recurrent Abdominal Pain: A Case Report and Review of the Literature - Can İhsan Öztorun; Rabia Demir; Esra Karakuş; Ceyda Kırsaçlıoğlu Tuna; Süleyman Arif Bostancı; Atilla Şenaylı; Müjdem Nur Azılı; Emrah Şenel (Haseki Tıp Bülteni)
Multiseptate gallbladder is a rare congenital malformation. It was first described by Simon and Tandon in 1963. A 1-year-old boy was admitted to our clinic with the complaints of intermittent abdominal pain and itching. Physical examination was normal; in laboratory tests, only liver enzymes (aspartate aminotransferase: 442 U/L, alanine aminotransferase: 270 U/L) and gamma glutamyl transpeptidase (73 U/L) were elevated. Ultrasonography (USG) showed a multiloculated gallbladder measuring approximately 41x33x46 mm in size with structures of septation with echogenic density contents. On magnetic resonance cholangiopancreatography (MRCP), a multiseptated cystic lesion approximately 90x50x80 mm in size was observed in the inferomedial aspect of the liver. Laparoscopic cholecystectomy was performed. Macroscopic evaluation demonstrated multiple septa dividing the gallbladder into compartments of different sizes. In the post-operative follow-up, liver enzymes fell within the normal range. Multiseptate gallbladder is a very rare congenital anomaly. In most cases, colic pain and nausea are observed. USG, computed tomography, MRCP, endoscopic retrograde cholangio-pancreatography, and hepatobiliary scintigraphy can be used in diagnosis. Cholecystectomy is preferred in the treatment of patients presenting with biliary colic. Asymptomatic cases do not require surgery; follow-up ultrasound scans are recommended. Multiseptate gallbladder should be considered in the differential diagnosis of acute cholecystitis and cholecystitis, in patients with intermittent right upper quadrant pain.